PENGGUNAAN ANIMATION MAKER UNTUK MENGEMBANGKAN KREATIFITAS SISWA DALAM PEMBELAJARAN SENI RUPA KELAS IV A SDN SUKO 363 - Dian Puspika Sari; Julianto; Abdul Rachman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to determine the contribution of animation maker learning media to students' creativity. The type of research used is Classroom Action Research (PTK) with the Kemmis and Taggart model research design. The subjects of this research were 27students in class IV A at SDN Suko 363, Sukodono Sidoarjo District. Data collection techniques were carried out using non-tests. The data collection tool uses non-tests with drawing creativity questionnaire sheets. Data were analyzed using quantitative descriptive techniques. The results of the Pre-Cycle research showed that the percentage of fluency indicators reached 58%, the flexibility indicator 51.8%, the authenticity indicator 53% and the elaboration indicator only reached 49.3%, the completion percentage only reached 3.7%. In cycle 1, the percentage of fluency indicators increased to 77.7%, the flexibility indicator reached 64.1%, the authenticity indicator reached 75.3%, the elaboration indicator reached 64.1%, the percentage of completeness in class drawing creativity also increased to 44.4%. In cycle 2, the percentage of the fluency indicator greatly increased to 96.2%, the flexibility indicator 90.1%, the authenticity indicator 93.8%, and the elaboration indicator 81.4%, the percentage of completeness in class drawing creativity also increased to 81.4%. Thus, the results of this research show that the application of the Animation Maker learning media can increase the drawing creativity of class IV A students at SDN Suko 363 Sukodono Sidoarjo.